Activation energy’s effect on nanofluid motion with double diffusion of Cattaneo–Christov in the Riga plate’s boundary layer - Saeed M. Ali; Nabil T.M. Eldabe; Abdulkafi M. Saeed; Mahmoud E. Ouaf (Alexandria Engineering Journal)
To close the gap between the various fluid flow investigations conducted within the boundary layer over the stretching plate, we have generalized the previous cases in this study with new additions. Thus, this study investigates the complex interactions among several parameters, including activation energy, the modified Darcy’s law, viscous dissipation, and heat and mass flux, based on the Cattaneo–Christov model, in the boundary layer over a Riga plate in a Casson nanofluid. Furthermore, the effects of thermal radiation and convective boundary conditions for concentration are taken into account to optimize heat and mass transfer. The approach involves formulating mathematical models, which are transformed into a set of nonlinear partial differential equations to simulate these intricate phenomena. These equations are then reduced to ordinary differential equations using a similarity transformation and solved via the homotopy perturbation method. The study reveals that magnetic, thermal, and mass transfer parameters significantly impact fluid behavior over a Riga plate. Velocity rises with the modified Hartmann number and permeability parameter. Temperature increases with thermophoresis and heat flux, while concentration grows with mass flux and activation energy. Additionally, skin friction and Nusselt number increase with permeability and non-Newtonian effects, while the Sherwood number rises with Brownian motion and heat flux.